Case Report: A family of fluctuating cystoid macular edema caused by MYO7A gene mutations - Duan, Cong; Zong, Yuan; Chen, Qian; Liu, Wei; Chang, Qing; Xiong, Cheng; Hu, Zhu-Lin; Xu, Ge-Zhi; Gao, Feng-Juan (Frontiers in Medicine, 2025)
Cystoid macular edema (CME) is a common complication in various retinal disorders, often leading to significant central vision impairment. However, the underlying genetic causes and detailed clinical features in patients with fluctuating CME remain unclear. This retrospective, observational case series analyzed two patients from a single family with fluctuating CME, focusing on both clinical and genetic aspects. Data were collected and analyzed from September 2022 to January 2023 at a single center. Comprehensive ocular examinations, including best-corrected visual acuity tests, color fundus photography, fundus fluorescein angiography (FFA), optical coherence tomography (OCT), visual field tests, flash electroretinography, multifocal electroretinography, and electrooculography, were performed. Genetic analysis was conducted using whole exome sequencing, with confirmation through Sanger sequencing and co-segregation analysis. The results identified two compound heterozygous variants in the MYO7A gene: c.562C>G p.Q188E and c.5929C>T p.R1977W in both patients. Fundus fluorescein angiography revealed cystoid hyperfluorescence in a petaloid pattern in the foveal area and a honeycomb pattern parafoveally. OCT showed that macular cystoid changes were primarily located in the outer nuclear layer (ONL), and full-field electroretinography indicated rod-cone dysfunction. Over a 108-day follow-up period, CME in both patients exhibited fluctuating changes without any treatment. This case series suggests that the identified MYO7A variants are likely associated with fluctuating CME, expanding the phenotypic spectrum of MYO7A and providing new insights into the mechanisms underlying CME. Identifying these MYO7A variants bridges genetic research with clinical diagnostics, potentially offering more precise and personalized treatment strategies for retinal disorders.